Предмет: Алгебра,
автор: vishenka20011
Решите пожалуйста))))
Приложения:
Ответы
Автор ответа:
0
6^(2n-3)*(1/3) ^(-n) / 108 ^ (n -2) = 6^(2n)*6⁻³ *(3⁻¹) ^(-n) / (108 ^n )*108⁻² =
(6²)^n * 3^ ((-1)*(-n) ) *6⁻³ *108² / (36 *3 ) ^n =
36^n * 3^ n *6⁻³ *(36*3)² / (36^n *3^n) =6 ⁻³ *(6²)²*3² =6 ⁻³ *6⁴*9 =6*9 =54.
(6²)^n * 3^ ((-1)*(-n) ) *6⁻³ *108² / (36 *3 ) ^n =
36^n * 3^ n *6⁻³ *(36*3)² / (36^n *3^n) =6 ⁻³ *(6²)²*3² =6 ⁻³ *6⁴*9 =6*9 =54.
Похожие вопросы
Предмет: Другие предметы,
автор: sams71seedrf
Предмет: Английский язык,
автор: Filka7
Предмет: Алгебра,
автор: luna244
Предмет: Алгебра,
автор: parxomceva9997
Предмет: Алгебра,
автор: nokdaoon